Bioreactor Co-Cultivation of High Lipid and Carotenoid Producing Yeast Rhodotorula kratochvilovae and Several Microalgae under Stress - Szotkowski, Martin; Holub, Jiří; Šimanský, Samuel; Hubačová, Klára; Sikorová, Pavlína; Mariničová, Veronika; Němcová, Andrea; Márová, Ivana (Microorganisms, 2021)
The co-cultivation of red yeasts and microalgae works with the idea of the natural transport of gases. The microalgae produce oxygen, which stimulates yeast growth, while CO2 produced by yeast is beneficial for algae growth. Both microorganisms can then produce lipids. The present pilot study aimed to evaluate the ability of selected microalgae and carotenogenic yeast strains to grow and metabolize in co-culture. The effect of media composition on growth and metabolic activity of red yeast strains was assessed simultaneously with microalgae mixotrophy. Cultivation was transferred from small-scale co-cultivation in Erlenmeyer flasks to aerated bottles with different inoculation ratios and, finally, to a 3L bioreactor. Among red yeasts, the strain R. kratochvilovae CCY 20-2-26 was selected because of the highest biomass production on BBM medium. Glycerol is a more suitable carbon source in the BBM medium and urea was proposed as a compromise. From the tested microalgae, Desmodesmus sp. were found as the most suitable for co-cultivations with R. kratochvilovae. In all co-cultures, linear biomass growth was found (144 h), and the yield was in the range of 8.78-11.12 g/L of dry biomass. Lipids increased to a final value of 29.62-31.61%. The FA profile was quite stable with the UFA portion at about 80%. Around 1.98-2.49 mg/g CDW of carotenoids with torularhodine as the major pigment were produced, ubiquinone production reached 5.41-6.09 mg/g, and ergosterol yield was 6.69 mg/g. Chlorophyll production was very low at 2.11 mg/g. Pilot experiments have confirmed that carotenogenic yeasts and microalgae are capable of symbiotic co-existence with a positive impact om biomass growth and lipid metabolites yields.
Keywords: Desmodesmus sp; co-cultivation; microalgae; lipids; Rhodotorula kratochvilovae; carotenoids; carotenogenic yeasts